Provision and staffing of NHS occupational health services in England and Wales. Issue 10 (1st October 1999) - Hughes, A; Philipp, R; Harling, K
Abstract : OBJECTIVES: To establish the extent of Occupational Health (OH) service provision in the National Health Service (NHS). METHODS: Two postal questionnaires were used to obtain information from purchasers and providers in the NHS in England and Wales. RESULTS: 99.6% of trust and health authority employers claim to provide some form of OH service to their employees indicating widespread recognition of need, but virtually no service is provided to other staff such as general practitioners (GPs), general dental practitioners (GDPs), and their staff. There is a wide variability in the range and quality of OH services, suggested by the enormous differences in medical staffing levels, and the contractual restrictions where the OH service is provided by another NHS employer. Only about a third (highest estimate) to a quarter (lowest estimate) of NHS staff have access to a specialist occupational physician. CONCLUSIONS: Substantial inequality of access to OH services exists for the NHS workforce, despite previous guidance. There is no real evidence to suggest why the extent of provision of OH services varies so greatly between institutions.